Carbon-carbon composite material with temperature-resistant sealing performance as well as preparation method and application of carbon-carbon composite material
By introducing specific non-carbon element nanoparticles and layered graphite sheet clusters into the carbon-carbon composite materials, the problems of single morphology and insufficient temperature resistance and sealing performance of carbon-carbon composite materials in the prior art are solved, and efficient high temperature resistance and sealing performance are achieved.
Patent Information
- Application Number
- CN202311353253.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The finished products of existing carbon-carbon composite materials have a single form, and the main constituent elements are only a single carbon element. The temperature-resistant and sealing performance is poor, and there is a lack of research on high aspect ratio and fiber rod-shaped morphology.
A cluster of layered graphite sheets with concentric circular structures is used as the matrix, and specific non-carbon element nanoparticles, including iron, aluminum, phosphorus, lead, cobalt, calcium and indium, are added to form a carbon-carbon composite material in an inert atmosphere through high temperature reaction.
The high temperature resistance and sealing performance of carbon-carbon composite materials are significantly improved, making them suitable for sealing applications in high-temperature environments.
Smart Images

Figure CN119843484A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a carbon-carbon composite material with temperature-resistant sealing performance and a preparation method and application thereof. Background Art
[0002] Carbon fiber has comprehensive properties such as high tensile strength, high tensile modulus, low density, high temperature resistance, ablation resistance, corrosion resistance, high electrical and thermal conductivity, low thermal expansion, self-lubrication and good biocompatibility. Carbon fiber is widely used in aerospace, automotive industry, building energy and sports equipment. He Fu wrote in the fifth chapter of Carbon Fiber and Graphite Fiber (first edition in September 2010): Graphite fiber generally refers to carbon fiber with a carbon content of more than 99%. Carbon fiber can be obtained by high-temperature graphitization at 2200-3000℃. Graphite fiber not only has a high carbon content, but also has a high tensile modulus. Graphite fiber has excellent properties such as low thermal expansion coefficient, good thermal stability and dimensional stability. Therefore, it is used to manufacture rigid, thin and dimensionally stable composite materials and is widely used in the field of aerospace based on spacecraft. For example, the horn antenna of artificial satellites is made of high-model carbon fiber composite materials to ensure dimensional stability in the space environment with alternating temperature.
[0003] Carbon-carbon (C / C) composite material refers to a multiphase structural material with carbon fiber or its fabric as the reinforcing phase, pyrolytic carbon infiltrated by chemical vapor phase or liquid phase impregnation-carbonized resin carbon and asphalt carbon as the matrix (domestic patent: CN112125690A). It has extremely high specific strength and specific modulus. It can be used above 2000℃ in an inert atmosphere without reducing the mechanical properties. It has unparalleled characteristics of any other material. C / C composite materials are non-melting and non-combustible, and are evenly ablated. They are widely used in the outer wall materials of space shuttles, missile nose cones, and engine nozzles. C / C composite materials are excellent thermal conductive materials with small thermal expansion coefficients, friction resistance and wear resistance, and are widely used in aircraft brake devices. C / C composite materials are prepared by preforms made of carbon fiber filaments, or short-cut carbon fiber composite matrix carbon as embryos, which are densified by liquid phase impregnation and carbonization or chemical vapor deposition and chemical vapor infiltration.
[0004] The manufacture of carbon-carbon composites is an integration of high-temperature technology and high-temperature equipment. The key technology of its continuous graphitization preparation is to inhibit and regulate the high-temperature oxidation and high-temperature biochemistry (evaporation) of graphite heating elements and running fibers. Carbon-carbon composites have different forms of carbon materials in macroscopic terms because of different forms of stacking / arrangement in the three-dimensional space. These various forms of carbon materials are composed of microcrystals of different sizes and diverse orientations and stacking states. The nanocarbon fibers grown by catalytic vapor phase have different shapes. Different catalysts and raw materials produce tubular, herringbone and flat nanocarbon fibers with different structures.
[0005] CN111807853A discloses a preparation process and application of carbon-carbon composite parts, which uses carbon fiber, vapor deposition carbon and impregnation carbon composite, can maintain good mechanical, thermal and friction and wear properties at high temperature, reduce costs by 50%, and can be mass-produced. CN112125690A uses flake graphite and UV silica gel to prepare a mixed colloid, fills it in the middle of the mixed layer of carbon fiber and glass fiber to prepare an intermediate, and prepares a carbon-carbon composite material by hot pressing, curing and drying. The composite material has the advantages of high tensile strength and high elasticity. CN112679950A discloses a preparation method of a flexible carbon-carbon composite material, after covering the surface of the carbon fiber cloth with a thermosetting resin film, hot pressing and curing are carried out, and the composite material is obtained after carbonization in an inert atmosphere. The method has the advantages of short processing time, simple process, no need for high-pressure equipment, and high production efficiency, and can realize industrial production. CN113175565A discloses a thin-walled high-strength carbon-carbon composite pipe and a preparation method thereof, the pipe comprises a pipe body formed by laminating carbon cloth, a binder, and a CVD layer, and a dense layer located on the inner surface of the pipe body, the pipe has the advantages of reducing the wall thickness while maintaining the strength. CN113636854A discloses a carbon-carbon composite material with deposited carbon nanotubes, wherein chopped carbon fibers are embedded in a carbon matrix and carbon fibers, and carbon nanotubes are deposited between the two, which has the advantages of significantly improving the mechanical properties and anti-oxidation properties of the carbon-carbon composite material. CN113636855A discloses an internal anti-oxidation carbon-carbon composite material, comprising a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, silicon carbide, zirconium oxide, and aluminum oxide, which has the advantages of improving the flame retardant sealing properties and service life of the composite material. CN113683437A discloses a carbon-carbon composite material containing refractory metals, including a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, a metal zirconium-fullerene composite nanopowder, and silicon-rich silicon carbide, which has the advantages of improving the flame retardant sealing performance, service life and antioxidant performance of the composite material. Patents CN113636855A and CN113683437A prepare ablation-resistant carbon-carbon composite materials through 7 different operation steps, and the preparation process is relatively cumbersome; the experimental conditions used are relatively harsh and time-consuming. CN115180969A discloses a high thermal conductivity carbon-carbon composite material and its preparation method, which produces graphene / AIN reinforcement on the surface and inside of a carbon fiber needle-punched preform by electrophoresis, impregnates it in a benzoxazine resin, and after thermal curing and atmospheric pressure carbonization, it has the advantages of excellent mechanical properties and good thermal conductivity. CN115231941A relates to a carbon-carbon composite material for ultra-high temperature environment and a preparation method thereof, comprising a carbon matrix, a carbon fiber reinforcement, ultra-high temperature ceramics and carbon nanotubes. The prepared carbon-carbon composite material has the advantages of excellent mechanical properties, high temperature ablation resistance and good thermal conductivity.CN213628313U discloses a carbon-carbon composite material plate, which has the advantages of light weight and high strength, high thermal conductivity and low expansion, good friction performance, good thermal shock resistance and high dimensional stability.
[0006] Existing public patent research shows that most of the current research work on C / C composite materials focuses on the improvement and optimization of their preparation process; focusing on solving the functional properties and application technical problems of C / C composite materials. However, the finished product form of C / C composite materials disclosed in the prior art is relatively simple, and the main component element is only carbon, the temperature resistance and sealing performance are poor, and there are no reports on C / C composite materials with high aspect ratio and fiber rod morphology. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems in the prior art that the finished products of carbon-carbon composite materials are of single form, the main component element is only a single carbon element, and the heat resistance and sealing performance are poor. A carbon-carbon composite material with heat resistance and sealing performance and its preparation method and application are provided. The carbon-carbon composite material is composed of layered graphite flake clusters with a concentric circle structure on a microscopic scale. In addition to carbon, it also contains specific non-carbon element nanoparticles, and the non-carbon elements are uniformly distributed at the atomic scale. The carbon-carbon composite material with this feature has excellent heat resistance and sealing performance.
[0008] In order to achieve the above-mentioned object, the present invention provides a carbon-carbon composite material with heat-resistant sealing performance, the carbon-carbon composite material comprising a single carbon fiber and a multilayer graphite sheet surrounding the outer periphery of the single carbon fiber, the surface of the single carbon fiber and each layer of graphite sheet is attached with non-carbon element nanoparticles,
[0009] The non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, optional Group IIA elements and optional indium.
[0010] Preferably, the carbon-carbon composite material contains 50-90 weight % of carbon, 0.5-10 weight % of iron, 0.5-10 weight % of aluminum, 0.2-5 weight % of phosphorus, 0.2-5 weight % of lead, 0.2-5 weight % of cobalt, 0-1 weight % of Group IIA elements and 0-1 weight % of indium.
[0011] Preferably, the carbon-carbon composite material contains 56-80 weight % of carbon, 5-8 weight % of iron, 4-8 weight % of aluminum, 1-3.5 weight % of phosphorus, 1-3.5 weight % of lead, 0.5-3.5 weight % of cobalt, 0.2-0.8 weight % of Group IIA elements and 0.2-0.8 weight % of indium.
[0012] Preferably, the Group IIA element is one or more selected from the group consisting of calcium, strontium and barium.
[0013] Preferably, the non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, calcium and indium.
[0014] Preferably, the number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, more preferably 6-12 layers.
[0015] Preferably, the diameter of the single carbon fiber is 4-8 um, preferably 4.5-7.5 um; the length is 2-10 mm, preferably 3-9 mm.
[0016] Preferably, the thickness of the multi-layer graphite sheet gradually increases from the inside to the outside.
[0017] Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:1.
[0018] Preferably, the carbon-carbon composite material is in a linear shape and / or a curved shape.
[0019] Preferably, at least a portion of the surface of the carbon-carbon composite material is in a bamboo-node shape and / or a convex shape.
[0020] Preferably, the carbon-carbon composite material has a diameter of 0.05-1 mm, preferably 0.1-0.3 mm, and a length of 0.1-10 mm, preferably 1-5 mm.
[0021] Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1.
[0022] Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak is 0.2-0.9:1.
[0023] The second aspect of the present invention provides a method for preparing a carbon-carbon composite material with heat-resistant sealing performance, the method comprising: reacting chopped carbon fibers, a carbon source, a metal source and a phosphorus source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 20-1800 mL / min;
[0024] The metal source contains an iron source, an aluminum source, a lead source, a cobalt source, an optional Group IIA element source and an optional indium source.
[0025] Preferably, the weight ratio of the metal source, the phosphorus source, the carbon source and the chopped carbon fiber is 20-100:3-20:30-200:1, preferably 30-70:5-15:50-150:1;
[0026] The weight ratio of the iron source, the aluminum source, the lead source, the cobalt source, the Group IIA element source and the indium source is 0.8-4:1-4:0.3-1.5:1:0-1:0-0.5.
[0027] Preferably, the Group IIA element source is selected from one or more of a calcium source, a strontium source and a barium source.
[0028] Preferably, the metal source contains an iron source, an aluminum source, a lead source, a cobalt source, a calcium source and an indium source.
[0029] Preferably, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4.
[0030] Preferably, the aluminum source is selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4.
[0031] Preferably, the lead source is selected from one or more of PbO, Pb3O4, PbO2 and Pb2O3.
[0032] Preferably, the cobalt source is selected from one or more of CoO, Co(OH)2, CoCl2 and CoSO4.
[0033] Preferably, the calcium source is selected from one or more of CaCl2, CaO, Ca(OH)2 and CaF2.
[0034] Preferably, the indium source is selected from one or more of In2O3, In(OH)3 and InCl3.
[0035] Preferably, the phosphorus source is selected from one or more of FePO4, AlPO4, Al(PO3)3 and Ca3(PO4)2.
[0036] Preferably, the carbon source is carbonized resin and / or graphite.
[0037] Preferably, the graphite is amorphous graphite.
[0038] Preferably, the reaction temperature is 1500-3000° C.; the reaction time is 12-720 hours, preferably 24-120 hours.
[0039] Preferably, the volume flow rate of the inert atmosphere is 50-500 mL / min, preferably 100-300 mL / min.
[0040] Preferably, the length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95% by weight.
[0041] The third aspect of the present invention provides a carbon-carbon composite material having heat-resistant sealing properties prepared by the method described above.
[0042] A fourth aspect of the present invention provides a use of the aforementioned carbon-carbon composite material with heat-resistant sealing properties as a heat-resistant sealing material.
[0043] The carbon-carbon composite material of the present invention is composed of a layered graphite sheet cluster with a concentric circle structure at a microscopic scale, and contains specific non-carbon element nanoparticles in addition to carbon, and the non-carbon element nanoparticles also contain specific metal elements and phosphorus elements, and the non-carbon elements are uniformly distributed in the graphite sheet cluster with a specific structure at the atomic scale; the carbon-carbon composite material with this feature has excellent high temperature resistance and sealing performance. Preferably, the carbon-carbon composite material containing iron, aluminum, lead, cobalt, calcium, indium and phosphorus elements at the same time has better high temperature resistance and sealing performance.
[0044] The method for preparing a carbon-carbon composite material with heat-resistant and sealing properties described in the present invention is simple to operate, and short chopped carbon fibers, a carbon source, a metal source and a phosphorus source are mixed and reacted directly under specific conditions to obtain a carbon-carbon composite material with excellent high temperature resistance and sealing properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Schematic diagram of the macroscopic morphology of the carbon-carbon composite material of Example 1.
[0046] Figure 2-Figure 8 They are the element distribution (element energy spectrum) of Fe, Al, P, Pb, Co, Ca and In inside the carbon-carbon composite material of Example 1 respectively.
[0047] Fig. 9 This is a schematic diagram of the cross-sectional morphology structure of the carbon-carbon composite material of Example 1.
[0048] Fig.10 This is a schematic diagram of a device for testing sealing performance according to the present invention.
[0049] Description of Reference Numerals
[0050] 1. Fixing fixture; 2. First container; 3. Second container; 4. Gas collection bottle; 5. Pipeline; 6. Gas inlet; 7. Sample piece. DETAILED DESCRIPTION
[0051] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0052] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0053] A first aspect of the present invention provides a carbon-carbon composite material with heat-resistant sealing properties, the carbon-carbon composite material comprising a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, the surfaces of the single carbon fiber and each layer of graphite sheets being attached with non-carbon element nanoparticles.
[0054] The carbon-carbon composite material provided by the present invention has a special microscopic morphology, in which a single carbon fiber is at the center of the carbon-carbon composite material, and a plurality of graphite sheets with a concentric circle structure are surrounded by the outer periphery of the single carbon fiber. Based on this special morphology, non-carbon element nanoparticles containing specific elements can be attached to the surface of the single carbon fiber and each layer of graphite sheets, so that there are non-carbon element nanoparticles between any two layers of graphite sheets and between the single carbon fiber and the first layer of graphite sheets, thereby ensuring that the non-carbon element nanoparticles are evenly distributed in the carbon-carbon composite material, thereby ensuring that the carbon-carbon composite material has good temperature resistance and sealing performance.
[0055] Specifically, the non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, optional Group IIA elements and optional indium; non-carbon element nanoparticles containing these specific elements are attached between any two layers of graphite sheets and between a single carbon fiber and the first layer of graphite sheets. Through the synergistic effect of these specific non-carbon elements, the high temperature resistance and sealing performance of the carbon-carbon composite material can be improved.
[0056] In the present invention, the Group IIA element is not particularly limited. In some preferred embodiments, the Group IIA element is selected from one or more of calcium, strontium and barium, preferably calcium.
[0057] In a preferred embodiment, the non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, calcium and indium at the same time. The combination of these specific non-carbon elements can further improve the high temperature resistance and sealing performance of the carbon-carbon composite material through synergistic effect.
[0058] In order to ensure that the carbon-carbon composite material has both excellent electrical conductivity and excellent high temperature resistance and sealing performance, the content of each element in the carbon-carbon composite material should be appropriate.
[0059] In some embodiments, the carbon-carbon composite material contains 50-90 weight % of carbon, 0.5-10 weight % of iron, 0.5-10 weight % of aluminum, 0.2-5 weight % of phosphorus, 0.2-5 weight % of lead, 0.2-5 weight % of cobalt, 0-1 weight % of Group IIA elements and 0-1 weight % of indium.
[0060] In a preferred embodiment, the carbon-carbon composite material contains 56-80% by weight of carbon, 5-8% by weight of iron, 4-8% by weight of aluminum, 1-3.5% by weight of phosphorus, 1-3.5% by weight of lead, 0.5-3.5% by weight of cobalt, 0.2-0.8% by weight of IIA group elements and 0.2-0.8% by weight of indium. Limiting the content of each element in the carbon-carbon composite material to this range can further improve the high temperature resistance and sealing performance of the carbon-carbon composite material.
[0061] In a preferred embodiment, the number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, more preferably 6-12 layers. When the number of graphite sheets with a concentric circle structure surrounding the outer periphery of the single carbon fiber is large, the non-carbon element nanoparticles can be distributed more evenly between the graphite sheets, thereby improving the high temperature resistance and sealing performance of the carbon-carbon composite material.
[0062] In the present invention, the diameter of the single carbon fiber can be a conventional choice in the art. In some embodiments, the diameter of the single carbon fiber can be 4-8 um, preferably 4.5-7.5 um.
[0063] The length of the single carbon fiber is comparable to the length of the carbon-carbon composite material; in some preferred embodiments, the length of the single carbon fiber may be 2-10 mm, preferably 3-9 mm.
[0064] The microscopic morphology of the carbon-carbon composite material described in the present invention is quite special. It can be seen from the scanning electron microscope that, under preferred circumstances, the thickness of the multilayer graphite sheets gradually increases from the inside to the outside, which can improve the stability of the concentric circle structure of the carbon-carbon composite material, thereby improving the high temperature resistance and sealing performance of the carbon-carbon composite material.
[0065] The approximate ratio of the volume content of carbon fiber and graphite sheet in the carbon-carbon composite material can be inferred from the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber. In a preferred embodiment, the ratio of the total thickness of the multilayer graphite sheet to the diameter of the single carbon fiber can be 1-100:1. Limiting the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber within this range can improve the dimensional stability of the concentric circle structure of the carbon-carbon composite material, maintain the uniform dispersion and firm bonding between the layered graphite sheet clusters, carbon fibers and non-carbon element nanoparticles, and thus improve the high temperature resistance and sealing performance of the carbon-carbon composite material.
[0066] In the present invention, the appearance of the carbon-carbon composite material is not limited and can be in various forms. Specifically, the carbon-carbon composite material is linear and / or curved as a whole.
[0067] The carbon-carbon composite material provided by the present invention further contains carbon particles existing independently or in aggregated form, wherein the carbon particles can be observed on the surface of the carbon-carbon composite material. Preferably, the particle size of the carbon particles is 0.02-2 mm.
[0068] In the present invention, due to the presence of non-carbon element nanoparticles, the diameter of the carbon-carbon composite material is not uniform. Specifically, at least part of the surface of the carbon-carbon composite material is in a bamboo-like shape and / or a convex shape.
[0069] In a specific embodiment, the carbon-carbon composite material may have a diameter of 0.05-1 mm, preferably 0.1-0.3 mm; and a length of 0.1-10 mm, preferably 1-5 mm.
[0070] In the present invention, specifically, through Raman spectrum characterization, the peak intensity ratio of the D peak to the G peak of the carbon-carbon composite material can be 0.07-0.3: 1. When the peak intensity ratio of the D peak to the G peak is within this range, the carbon atom lattice defect is small, and the graphitization degree of the carbon-carbon composite material is relatively complete.
[0071] In the present invention, specifically, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak can be 0.2-0.9:1. When the peak intensity ratio of the 2D peak to the G peak is within this range, the carbon atoms have few lattice defects, the layered graphite sheet clusters have a complete and regular graphite structure, and the formed carbon-carbon composite material has both high temperature resistance and sealing performance.
[0072] Furthermore, the carbon-carbon composite material of the present invention is grey or black.
[0073] The carbon-carbon composite material of the present invention also contains a small amount of other non-carbon elements, including zinc, manganese, silver, barium, copper, lithium, magnesium, lead and strontium, and the total content of each metal element is less than 0.001% by weight.
[0074] In addition to the aforementioned elements, the carbon-carbon composite material of the present invention also contains elements such as oxygen, nitrogen, and sulfur. The metal elements in the carbon-carbon composite material may exist in the form of compounds, and the phosphorus element may exist in the form of phosphate.
[0075] The second aspect of the present invention provides a method for preparing a carbon-carbon composite material with heat-resistant sealing performance, the method comprising: reacting chopped carbon fibers, a carbon source, a metal source and a phosphorus source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 20-1800 mL / min,
[0076] The metal source comprises an iron source, an aluminum source, a lead source, a cobalt source, an optional Group IIA element source and an optional indium source.
[0077] The method of the present invention is simple and easy to operate, and only requires that the chopped carbon fibers, a carbon source, a specific metal source and a phosphorus source be reacted under specific conditions.
[0078] In the method described in the present invention, if the reaction temperature is too low, graphite sheets with a concentric circle structure cannot be formed outside the carbon fiber, resulting in the inability of specific non-carbon element nanoparticles to adhere in large quantities and evenly to the graphite sheets and carbon fiber surfaces, thereby resulting in poor high temperature resistance and sealing performance of the prepared material; if the reaction temperature is too high, the growth rate of the graphite sheets on the carbon fiber surface is much faster than the speed at which the non-carbon element nanoparticles adhere to the graphite sheet layer, resulting in uneven distribution of the non-carbon element nanoparticles on the graphite sheets, which also results in poor heat resistance and sealing performance of the prepared material.
[0079] In some embodiments, the reaction temperature may be 1500° C., 1800° C., 2000° C., 2200° C., 2500° C., 2800° C., 3000° C., 3200° C. or 3500° C. In a preferred embodiment, the reaction temperature is 1500-3000° C.
[0080] In some embodiments, the reaction time can be 12-720 hours. In a preferred embodiment, the reaction time is 24-120 hours, for example, 24 hours, 48 hours, 72 hours, 80 hours, 100 hours or 120 hours.
[0081] In order to ensure that the chopped carbon fibers, carbon source, specific metal source and phosphorus source can be used to prepare the carbon-carbon composite material of the above structure, the reaction needs to be carried out under inert atmosphere conditions. Specifically, the inert atmosphere is nitrogen and / or inert gas; the purity of nitrogen and inert gas is greater than 99.9% by volume, and the oxygen content in the inert atmosphere is less than 50ppm.
[0082] If there is no inert atmosphere for protection during the reaction, it is impossible to obtain a carbon-carbon composite material including a single carbon fiber and a multilayer graphite sheet surrounding the single carbon fiber, wherein the surface of the single carbon fiber and each layer of graphite sheet is attached with non-carbon element nanoparticles. In addition, if the volume flow rate of the inert atmosphere is too large, it is impossible to maintain a microenvironment for the stable growth of the graphite sheet, and the non-carbon element nanoparticles are even less able to attach to the surface of the carbon fiber or the graphite sheet.
[0083] In some embodiments, the volume flow rate of the inert atmosphere is 20-1800 mL / min. In a preferred embodiment, the volume flow rate of the inert atmosphere is 50-500 mL / min, more preferably 100-300 mL / min.
[0084] In the present invention, in order to obtain a carbon-carbon composite material with an appropriate ratio of carbon element to non-carbon element content, a large number of graphite sheets surrounding the diameter of a single carbon fiber, and excellent high temperature resistance and sealing properties, the usage ratio of chopped carbon fiber, carbon source, metal source and phosphorus source, as well as the usage ratio between the metal sources can be appropriately controlled.
[0085] In some embodiments, the weight ratio of the metal source, the phosphorus source, the carbon source and the chopped carbon fiber is 20-100:3-20:30-200:1, preferably 30-70:5-15:50-150:1;
[0086] The weight ratio of the iron source, the aluminum source, the lead source, the cobalt source, the Group IIA element source and the indium source is 0.8-4:1-4:0.3-1.5:1:0-1:0-0.5.
[0087] In the present invention, the function of the non-carbon element source is to generate non-carbon element nanoparticles, and attach to the surface of graphite sheets and single carbon fibers to improve the performance of carbon-carbon composite materials. Wherein, the IIA group element can be a conventional choice in the art, specifically, the IIA group element source is selected from one or more of a calcium source, a strontium source and a barium source, preferably a calcium source.
[0088] In a preferred embodiment, the metal source contains an iron source, an aluminum source, a lead source, a cobalt source, a calcium source and an indium source. Using an iron source, an aluminum source, a lead source, a cobalt source, a calcium source, an indium source and a phosphorus source as non-carbon element sources can further improve the high temperature resistance and sealing performance of the prepared carbon-carbon composite material.
[0089] In the present invention, the iron source can be a conventional choice in the art, for example, it can be an iron salt, an iron hydroxide or an iron oxide. Specifically, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4.
[0090] In the present invention, the aluminum source can be a conventional choice in the art, for example, aluminum salt, aluminum hydroxide or aluminum oxide. Specifically, the aluminum source is selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4.
[0091] In the present invention, the lead source can be a conventional choice in the art, for example, lead oxide. Specifically, the lead source is selected from one or more of PbO, Pb3O4, PbO2 and Pb2O3.
[0092] In the present invention, the cobalt source can be a conventional choice in the art, for example, a cobalt salt, a cobalt oxide or a cobalt hydroxide. Specifically, the cobalt source is selected from one or more of CoO, Co(OH)2, CoCl2 and CoSO4.
[0093] In the present invention, the calcium source can be a conventional choice in the art, for example, a calcium salt, a calcium oxide or a calcium hydroxide. Specifically, the calcium source is selected from one or more of CaCl2, CaO, Ca(OH)2 and CaF2.
[0094] In the present invention, the indium source can be a conventional choice in the art, such as an indium salt, an indium oxide or an indium hydroxide. Specifically, the indium source is selected from one or more of In2O3, In(OH)3 and InCl3.
[0095] In the method of the present invention, the role of the carbon source is to form a graphite sheet on the periphery of a single carbon fiber. The carbon source can be a conventional choice in the art, specifically, the carbon source can be a carbonized resin and / or graphite. Preferably, the carbonized resin is a resin carbide with a rich pore structure after high-temperature carbonization. Preferably, the graphite is amorphous graphite.
[0096] In the present invention, the reaction can be carried out in a conventional high-temperature furnace. Specifically, isostatic graphite or highly oriented graphite is used as a heating element in the high-temperature furnace. Preferably, the high-temperature furnace is connected to the tail gas recovery system through a pipeline, and a valve is provided on the pipeline connecting the high-temperature furnace and the tail gas recovery system. The inner diameter of the pipeline is between 5-20 mm. A filter is provided before the valve along the gas flow direction. The selection of the pipeline, the filter and the valve meets the temperature resistance requirements.
[0097] In the present invention, the single carbon fiber in the center of the carbon-carbon composite material is formed by chopped carbon fiber. In a specific embodiment, the length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95% by weight.
[0098] The third aspect of the present invention provides a carbon-carbon composite material having heat-resistant sealing properties prepared by the method described above.
[0099] Preferably, the carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, and non-carbon element nanoparticles are attached to the surfaces of the single carbon fiber and each layer of graphite sheets.
[0100] The non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, optional Group IIA elements and optional indium.
[0101] A fourth aspect of the present invention provides use of the aforementioned carbon-carbon composite material with heat-resistant sealing properties as a heat-resistant sealing material.
[0102] The present invention also provides a device for testing sealing performance, such as Fig.10 As shown, the device includes a fixing fixture 1, a first container 2, a second container 3, a gas collection bottle 4, a pipe 5 and a sample piece 7. The first container 2 is located below the second container 3. The upper surface of the first container 2 has a first opening, and the lower surface of the second container 3 has a second opening. The sample piece 7 is fixed between the first container 2 and the second container 3 to seal the first opening of the first container 2 and the second opening of the second container 3. The first container 2 has a gas inlet 6. The second container 3 is connected to one end of the pipe 5, and the other end of the pipe 5 is placed in the gas collection bottle 4.
[0103] When performing the sealing performance test, the gas collection bottle 4 is filled with water, and the trimmed sample piece 7 is fixed between the first container 2 and the second container 3 to seal the first opening of the first container 2 and the second opening of the second container 3, and then the gas is introduced from the gas inlet 6. The leakage degree of the carbon-carbon composite material sample piece is analyzed by the number of bubbles in the gas collection bottle 4 per minute to evaluate the sealing performance of the composite material. If the sealing performance of the sample piece 7 is good, the gas cannot enter the second container 3 from the first container 2, and then the number of bubbles in the gas collection bottle 4 is small. If the sealing performance of the sample piece 7 is good, the number of bubbles in the gas collection bottle 4 is large.
[0104] In the device for testing sealing performance of the present invention, if Fig.10 As shown, the height difference Δh between the end of the pipe 5 in the gas collection bottle 4 and the liquid level of the gas collection bottle 4 is 10-30 mm, preferably 20 mm.
[0105] Under preferred conditions, the gas introduced from the gas inlet 6 is nitrogen. Further, the pressure of the introduced nitrogen is 2 MPa.
[0106] Under preferred conditions, the inner diameter of the pipe 5 is 5-12 mm, preferably 8 mm.
[0107] The carbon-carbon composite material described in the present invention can be further processed as a raw material. The processing methods include but are not limited to blending (extrusion or granulation), strip making, grinding (crushing), and roasting. The types and contents of the constituent elements of the material products manufactured by the above-mentioned processing methods, as long as they fall within the scope of the claims and description of the present invention, belong to the protection scope of the present invention. It is further clarified that as long as the types and contents of the elements contained are within the specified scope of the present invention, whether it is a raw material or a finished product, and the shape of the material is not limited to a fiber shape; and it is not limited to the processing process of the material, it is within the protection scope of the present invention.
[0108] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. In the following examples, unless otherwise specified, all reagents used are commercially available.
[0109] In the following examples and comparative examples, the carbonized resin powder is YKD-508 hemoperfusion carbonized resin (carbon skeleton spherical porous adsorption resin) produced by Henan Yinkai New Materials Co., Ltd.
[0110] The test method adopted by the present invention comprises:
[0111] 1. The surface and cross-sectional morphology of the carbon-carbon composite materials prepared in the examples and comparative examples were observed using a ZEISS Merlin field emission scanning electron microscope, wherein the test conditions included: an acceleration voltage of 20 to 30 kV, and an electron beam current of 10 pA to 40 / 100 / 300 nA.
[0112] 2. The element types, distribution states and particle sizes of the carbon-carbon composite materials prepared in the examples and comparative examples were analyzed using an X-ray spectrometer configured with a field emission scanning electron microscope from German ZEISS Merlin. The surface scanning mode test conditions included: an acceleration voltage of 20 to 30 kV, an effective working area of the probe of 150 mm 2 , element range Be~U, detection limit ≈0.1wt.%.
[0113] 3. Raman imaging analysis of the cross section of carbon-carbon composite materials: A laser micro-Raman spectrometer (micro-Raman spectroscopy analysis, RENISHAW, inVia Raman microscope, UK, 532nm line, helium-neon laser radiation model: QONTOR) is used to observe the cross-sectional morphology of the carbon-carbon composite materials prepared in the embodiments and comparative examples, and Raman imaging analysis of the cross-sectional morphology is performed, which can achieve high-sensitivity spectral analysis under high-resolution conditions. The specific method includes: directly breaking the carbon-carbon composite material, observing the morphology after the cross section appears, using Live TrackTM technology to focus in real time, and collecting each point in the test process in a focused state. The coordinates of each point in the Z-axis direction will be recorded to form a height imaging map of the surface, and the Raman imaging results can be superimposed on the height map. The in-situ Raman imaging area: 70um*70um, step length 1um, the recording range of the Raman spectrum is 400-3100cm -1 The integration time of each spectrum is 100s. The cross-sectional morphology of the fibrous composite material was observed under a 20x objective lens, and the Raman spectrum was collected somewhere in the 1um*1um area. The spectrum has a wavelength of 1350cm -1 Nearby D peak, 1582cm -1 The nearby G peak, and 2699cm -1 The 2D peak nearby; also use Raman imaging to see the intensity distribution of the D peak at different points.
[0114] 4. The types and contents of non-carbon elements in the carbon-carbon composite materials prepared in the examples and comparative examples were tested using an inductively coupled plasma emission spectrometer.
[0115] The main instruments and reagents are as follows:
[0116] (1) Varian 725-ES inductively coupled plasma optical emission spectrometer;
[0117] (2) Haoyue HMF1600-40 box-type furnace;
[0118] (3) Labtech Digiblock ST36 electric heating digestion instrument;
[0119] (4) Multi-element standard solution: 1000ug / mL (Steel Research Institute of Testing Technology Co., Ltd.); praseodymium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); vanadium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); The ultrapure water used in the experiment was prepared by the Genie Purist intelligent ultrapure water system of Lefeng (resistivity = 18.2MΩcm, 25°C); hydrogen peroxide (30wt%), hydrochloric acid, nitric acid, and hydrofluoric acid were all of premium grade purity; sulfuric acid was of process ultrapure purity (Sinopharm Chemical Reagent Co., Ltd.); liquid argon (Chart Cryogenic Engineering Systems (Changzhou) Co., Ltd.).
[0120] The working conditions of the instrument are as follows:
[0121] Instrument operating parameters: high frequency power: 1100W; plasma gas flow rate: 15L min -1 ; Auxiliary gas flow: 1.5Lmin -1 ; Atomizing gas flow rate: 0.75L min -1 ; Injection pump speed: 15rpm; Observation height: 10mm.
[0122] The experimental method is as follows:
[0123] (1) Accurately weigh 0.1g of sample into a clean quartz crucible, place it in a box furnace, and gradually heat it to 930℃ for ash treatment to obtain ash. The weight percentage of the sample reduced during the calcination process is the carbon content of the fibrous carbon-carbon composite material in this patent;
[0124] (2) Use a small amount of ultrapure water to transfer all the ash into a PFA test tube, add aqua regia, hydrogen peroxide, sulfuric acid and hydrofluoric acid in sequence, cover and place in an electric heating digestion instrument to heat until the sample is completely digested;
[0125] (3) Remove the test tube and cool it to room temperature. Use ultrapure water to transfer it to a 50 mL volumetric flask and make up to volume for testing.
[0126] (4) Prepare a mixed standard solution of the elements, draw a test spectrum, use an inductively coupled plasma spectrometer to detect the solution to be tested, and calculate the content of each element according to the drawn test spectrum.
[0127] Example 1
[0128] The method for preparing the carbon-carbon composite material comprises:
[0129] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder, metal source and phosphorus source (AlPO4) were reacted in a high-temperature furnace for 48 hours.
[0130] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 50:7:100:1, and the weight ratio of the metal sources Fe2O3, Al2O3, Pb3O4, Co(OH)2, CaF2 and In2O3 is 1.7:1.3:1:1:0.2:0.1.
[0131] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.
[0132] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0133] The carbon-carbon composite material prepared in this embodiment (macroscopic morphology is shown in FIG. Figure 1 ), with the following characteristics:
[0134] (1) Fig. 9 As shown, the center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0135] (2) The carbon-carbon composite material is gray, and independent carbon particles are distributed on the surface of each graphite sheet and single carbon fiber, with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.161:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.484:1;
[0136] (3) The main elements contained in the carbon-carbon composite material include: C content is 59 weight %; Fe content is 5.0 weight %; Al content is 4.0 weight %; P content is 2.1 weight %; Pb content is 2.6 weight %; Co content is 2.8 weight %; Ca content is 0.5 weight %; In content is 0.3 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0137] The characteristics of step (1) and step (2) were obtained by using a ZEISS Merlin field emission scanning electron microscope and an X-ray energy spectrometer configured with a field emission scanning electron microscope of ZEISS Merlin, Germany;
[0138] from Figure 2-Figure 8 It can be seen from the element spectrum that the Fe( Figure 2 )、Al( Figure 3 )、P( Figure 4 )、Pb( Figure 5 )、Co( Figure 6 )、Ca( Figure 7 ) and In( Figure 8 ) are evenly distributed and are nanoparticles.
[0139] Example 2
[0140] The method for preparing the carbon-carbon composite material comprises:
[0141] In the presence of nitrogen, short-cut carbon fibers (24K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite, a metal source and a phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 100 hours.
[0142] The weight ratio of the metal source, phosphorus source, amorphous graphite and chopped carbon fiber is 33:5:70:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 2.4:2:1:1:0.2:0.2.
[0143] The high-temperature furnace uses highly oriented graphite as the heating element. The central temperature of the high-temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 200mL / min.
[0144] A valve is provided on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 5mm. A filter is provided before the valve along the gas flow direction.
[0145] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0146] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 7 layers of graphite sheets in a concentric circle structure, the thickness of the 7 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 7 layers of graphite sheets to the diameter of the single carbon fiber is 38:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 6mm;
[0147] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1.3 mm; the carbon-carbon composite material is linear in the axial direction, and block-shaped protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.163:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.477:1;
[0148] (3) The main elements contained in the carbon-carbon composite material include: C content is 63 weight %; Fe content is 6.7 weight %; Al content is 5.5 weight %; P content is 3.1 weight %; Pb content is 3.3 weight %; Co content is 3.2 weight %; Ca content is 0.7 weight %; In content is 0.6 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0149] Example 3
[0150] The method for preparing the carbon-carbon composite material comprises:
[0151] In the presence of nitrogen, short-cut carbon fibers (specification 50K, length 9 mm, carbon content 90 wt%), carbonized resin powder, metal source and phosphorus source (AlPO4) were reacted in a high-temperature furnace for 80 hours.
[0152] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 25:4:50:1, and the weight ratio of the metal sources Fe2O3, Al2O3, Pb3O4, Co(OH)2, CaF2 and In2O3 is 2.75:1.25:1:1:0.25:0.25.
[0153] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 400mL / min.
[0154] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 15mm. A filter is installed before the valve along the gas flow direction.
[0155] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0156] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 9mm; the outer periphery of the single carbon fiber is surrounded by 7 layers of graphite sheets in a concentric circle structure, the thickness of the 7 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 7 layers of graphite sheets to the diameter of the single carbon fiber is 39:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 9mm;
[0157] (2) The carbon-carbon composite material is gray, and independent carbon particles are distributed on the surface of each graphite sheet and single carbon fiber, and the particle size of the carbon particles is 0.08 mm; the carbon-carbon composite material is linear in the axial direction, and part of the surface is bamboo-like; in the Raman imaging spectrum of the carbon-carbon composite material, the ratio of the average value of the peak intensity of the D peak to the G peak is 0.183:1, and the ratio of the average value of the peak intensity of the 2D peak to the G peak is 0.554:1;
[0158] (3) The main elements contained in the carbon-carbon composite material include: C content is 55 weight %; Fe content is 8.2 weight %; Al content is 4.0 weight %; P content is 3.1 weight %; Pb content is 2.9 weight %; Co content is 3.0 weight %; Ca content is 0.4 weight %; In content is 0.8 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0159] Example 4
[0160] The method for preparing the carbon-carbon composite material comprises:
[0161] In the presence of nitrogen, short-cut carbon fibers (specification 12K, length 6mm, carbon content 95%), amorphous graphite, metal source and phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 150 hours.
[0162] The weight ratio of the metal source, the phosphorus source, the amorphous graphite and the chopped carbon fiber is 32:4:65:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 2.5:2:1.5:1:0.25:0.25.
[0163] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 500mL / min.
[0164] A valve is provided on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 20 mm. A filter is provided before the valve along the gas flow direction.
[0165] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0166] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 43:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.6mm, and the length is 6mm;
[0167] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1.1 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.179:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.553:1;
[0168] (3) The main elements contained in the carbon-carbon composite material include: C content is 68 weight %; Fe content is 7.5 weight %; Al content is 6.3 weight %; P content is 2.9 weight %; Pb content is 4.2 weight %; Co content is 3.1 weight %; Ca content is 0.6 weight %; In content is 0.8 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0169] Example 5
[0170] The method for preparing the carbon-carbon composite material comprises:
[0171] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite, a metal source and a phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 36 hours.
[0172] The weight ratio of the metal source, the phosphorus source, the amorphous graphite and the chopped carbon fiber is 23:3:45:1, and the weight ratio of the metal source FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 2:2:1:1:0.33:0.33.
[0173] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 50mL / min.
[0174] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0175] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0176] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 17 layers of graphite sheets with a concentric circle structure, the thickness of the 17 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 17 layers of graphite sheets to the diameter of the single carbon fiber is 65:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.9mm, and the length is 6mm;
[0177] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1.2 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.188:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.556:1;
[0178] (3) The main elements contained in the carbon-carbon composite material include: C content is 80 weight %; Fe content is 3.3 weight %; Al content is 3.2 weight %; P content is 1.5 weight %; Pb content is 1.7 weight %; Co content is 1.9 weight %; Ca content is 0.5 weight %; In content is 0.6 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0179] Example 6
[0180] The method for preparing the carbon-carbon composite material comprises:
[0181] In the presence of nitrogen, short-cut carbon fibers (specification 12K, length 6mm, carbon content 95%), amorphous graphite, metal source and phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 120 hours.
[0182] The weight ratio of the metal source, phosphorus source, amorphous graphite and chopped carbon fiber is 31:6:65:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 0.8:1.43:1:1:0.14:0.14.
[0183] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 100mL / min.
[0184] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0185] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0186] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 18 layers of graphite sheets with a concentric circle structure, the thickness of the 18 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 18 layers of graphite sheets to the diameter of the single carbon fiber is 95:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 1mm, and the length is 6mm;
[0187] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1.5 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.186:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.554:1;
[0188] (3) The main elements contained in the carbon-carbon composite material include: C content is 74 weight %; Fe content is 4.0 weight %; Al content is 7.2 weight %; P content is 4.2 weight %; Pb content is 4.4 weight %; Co content is 4.6 weight %; Ca content is 0.3 weight %; In content is 0.7 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0189] Example 7
[0190] The method for preparing the carbon-carbon composite material comprises:
[0191] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite, a metal source and a phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 144 hours.
[0192] The weight ratio of the metal source, the phosphorus source, the amorphous graphite and the chopped carbon fiber is 29:6:60:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 1.6:1.4:1:1:0.2:0.2.
[0193] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 200mL / min.
[0194] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0195] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0196] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 38:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 6mm;
[0197] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 0.6 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.184:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.555:1;
[0198] (3) The main elements contained in the carbon-carbon composite material include: C content is 63 weight %; Fe content is 7.0 weight %; Al content is 5.9 weight %; P content is 4.7 weight %; Pb content is 4.3 weight %; Co content is 4.0 weight %; Ca content is 0.4 weight %; In content is 0.9 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0199] Example 8
[0200] The method for preparing the carbon-carbon composite material comprises:
[0201] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite, a metal source and a phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 72 hours.
[0202] The weight ratio of the metal source, phosphorus source, amorphous graphite and chopped carbon fiber is 53:8:110:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 2.85:1.43:1.14:1:0.14:0.14.
[0203] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 400mL / min.
[0204] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0205] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0206] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 13 layers of graphite sheets in a concentric circle structure, the thickness of the 13 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 13 layers of graphite sheets to the diameter of the single carbon fiber is 49:1; non-carbon element nanoparticles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.5mm, and the length is 6mm;
[0207] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.183:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.555:1;
[0208] (3) The main elements contained in the carbon-carbon composite material include: C content is 52 weight %; Fe content is 9.0 weight %; Al content is 3.9 weight %; P content is 2.9 weight %; Pb content is 3.1 weight %; Co content is 2.5 weight %; Ca content is 0.1 weight %; In content is 0.4 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0209] Example 9
[0210] The method for preparing the carbon-carbon composite material comprises:
[0211] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite, a metal source and a phosphorus source (Al(PO3)3) were reacted in a high-temperature furnace for 48 hours.
[0212] The weight ratio of the metal source, phosphorus source, amorphous graphite and chopped carbon fiber is 79:4:160:1, and the weight ratio of the metal sources FeCl3, AlCl3, Pb2O3, CoCl2, CaCl2 and InCl3 is 4:4:0.4:1:0.8:0.2.
[0213] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 500mL / min.
[0214] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0215] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0216] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 16 layers of graphite sheets in a concentric circle structure, the thickness of the 16 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 16 layers of graphite sheets to the diameter of the single carbon fiber is 89:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.9mm, and the length is 6mm;
[0217] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1.2 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.179:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.554:1;
[0218] (3) The main elements contained in the carbon-carbon composite material include: C content of 72 weight %; Fe content of 8.0 weight %; Al content of 5.9 weight %; P content of 0.8 weight %; Pb content of 0.2 weight %; Co content of 0.6 weight %; Ca content of 0.7 weight %; In content of 0.2 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0219] Example 10
[0220] The method of Example 1 is followed, except that the metal sources are iron source, aluminum source, lead source, cobalt source and indium source, and no calcium source is included.
[0221] The method for preparing the carbon-carbon composite material comprises:
[0222] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder, metal source and phosphorus source (AlPO4) were reacted in a high-temperature furnace for 48 hours.
[0223] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 50:7:100:1, and the weight ratio of the metal sources Fe2O3, Al2O3, Pb3O4, Co(OH)2 and In2O3 is 1.75:1.38:1:1:0.13.
[0224] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.
[0225] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0226] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0227] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0228] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.182:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.553:1;
[0229] (3) The main elements contained in the carbon-carbon composite material include: C content is 58 weight %; Fe content is 5.2 weight %; Al content is 4.4 weight %; P content is 2.3 weight %; Pb content is 2.8 weight %; Co content is 2.9 weight %; In content is 0.4 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0230] Embodiment 11
[0231] The method of Example 1 is followed, except that the metal sources are iron source, aluminum source, lead source, cobalt source and calcium source, and no indium source is included.
[0232] The method for preparing the carbon-carbon composite material comprises:
[0233] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90 wt% carbon content), carbonized resin powder, metal source and phosphorus source (AlPO4) were reacted in a high temperature furnace for 48 hours.
[0234] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 50:7:100:1, and the weight ratio of the metal sources Fe2O3, Al2O3, Pb3O4, Co(OH)2 and CaF2 is 1.75:1.25:1:1:0.25.
[0235] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.
[0236] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0237] The carbon-carbon composite material prepared in this embodiment has the following characteristics:
[0238] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0239] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.180:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.550:1;
[0240] (3) The main elements contained in the carbon-carbon composite material include: C content is 57 weight %; Fe content is 5.2 weight %; Al content is 4.1 weight %; P content is 2.1 weight %; Pb content is 2.8 weight %; Co content is 3.2 weight %; Ca content is 0.8 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0241] Comparative Example 1
[0242] The method of Example 1 is followed, except that no chopped carbon fibers are added into the high-temperature furnace.
[0243] In this comparative example, due to the lack of chopped carbon fibers, the non-carbon element particles cannot form growth attachment points, and the carbon vapor can only grow into blocky carbon-containing materials with extremely high carbon content on the surface of the inner wall of the high-temperature furnace, and the carbon-carbon composite material described in the present invention cannot be obtained.
[0244] The material obtained in this comparative example is a bulk product formed by a carbon source, and the material contains 99.9% by weight of carbon, and does not contain iron, aluminum, phosphorus, lead, cobalt, calcium and indium.
[0245] Comparative Example 2
[0246] The method of Example 1 was followed, except that the reaction process was not protected by an inert atmosphere.
[0247] Due to the lack of inert atmosphere protection, the carbonized resin powder is oxidized into carbon dioxide, and the short-cut carbon fibers with higher temperature resistance are broken into short-cut carbon fibers with uneven shapes and oxidized and etched surfaces. It is impossible to form a concentric circle structure with multiple layers of graphite sheets surrounding a single carbon fiber, and it is impossible to fill non-carbon element particles. Therefore, the carbon-carbon composite material described in the present invention cannot be obtained.
[0248] The material prepared in this comparative example contains 99.9% by weight of carbon, and does not contain iron, aluminum, phosphorus, lead, cobalt, calcium, and indium.
[0249] Comparative Example 3
[0250] The method of Example 1 is followed, except that no carbonized resin powder and non-carbon element source are added into the high-temperature furnace.
[0251] The material obtained in this comparative example is a product formed by chopped carbon fibers, which contains 99.9% by weight of carbon, but does not contain iron, aluminum, phosphorus, lead, cobalt, calcium and indium, and the carbon-carbon composite material described in the present invention cannot be obtained.
[0252] Comparative Example 4
[0253] The method of Example 1 is followed, except that the center temperature is 1200°C.
[0254] In this comparative example, since the temperature is too low, the carbon in the carbonized resin powder cannot grow further on the surface of a single carbon fiber, and the non-carbon element particles cannot adhere to the surface of the carbon fiber or graphite sheet, and the carbon-carbon composite material of the present invention cannot be obtained.
[0255] The material prepared in this comparative example is a mixture formed by independent reactions of chopped carbon fibers, carbonized resin powder and metal source.
[0256] Comparative Example 5
[0257] The method of Example 1 was followed, except that the gas flow rate was 2000 mL / min.
[0258] In this comparative example, since the gas flow rate is too large, the microenvironment for the stable growth of graphite sheets cannot be maintained, and non-carbon element particles cannot adhere to the surface of carbon fibers or graphite sheets, and the carbon-carbon composite material of the present invention cannot be obtained.
[0259] The material prepared in this comparative example is a mixture formed by independent reactions of chopped carbon fibers, carbonized resin powder and metal source.
[0260] Comparative Example 6
[0261] The method of Example 1 is followed, except that no phosphorus source is added to the high-temperature furnace.
[0262] The carbon-carbon composite material prepared in this comparative example has the following characteristics:
[0263] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0264] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.160:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.481:1;
[0265] (3) The main elements contained in the carbon-carbon composite material include: C content is 59 weight %; Fe content is 5.0 weight %; Al content is 3.9 weight %; Pb content is 2.6 weight %; Co content is 2.8 weight %; Ca content is 0.5 weight %; In content is 0.3 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0266] Comparative Example 7
[0267] The method of Example 1 is followed, except that no metal source is added to the high temperature furnace.
[0268] The carbon-carbon composite material prepared in this comparative example has the following characteristics:
[0269] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0270] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.159:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.479:1;
[0271] (3) The main elements contained in the carbon-carbon composite material include: carbon content is 99.9 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0272] Comparative Example 8
[0273] The method of Example 1 is followed, except that no lead source Pb3O4 is added into the high temperature furnace.
[0274] The method for preparing the carbon-carbon composite material comprises:
[0275] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90 wt% in carbon content), the carbonized resin powder, the metal source and the phosphorus source (AlPO4) were reacted in a high temperature furnace for 48 hours.
[0276] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 50:7:100:1, and the weight ratio of the metal source Fe2O3, Al2O3, Co(OH)2, CaF2 and In2O3 is 1.5:1.17:1:0.33:0.17.
[0277] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.
[0278] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0279] The carbon-carbon composite material prepared in this comparative example has the following characteristics:
[0280] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; non-carbon element nanoparticles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0281] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.183:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.547:1;
[0282] (3) The main elements contained in the carbon-carbon composite material include: C content is 58 weight %; Fe content is 5.1 weight %; Al content is 4.2 weight %; P content is 2.0 weight %; Co content is 3.3 weight %; Ca content is 0.9 weight %; In content is 0.6 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0283] Comparative Example 9
[0284] The method of Example 1 is followed, except that no cobalt source Co(OH)2 is added to the high temperature furnace.
[0285] The method for preparing the carbon-carbon composite material comprises:
[0286] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder, metal source and phosphorus source (AlPO4) were reacted in a high-temperature furnace for 48 hours.
[0287] The weight ratio of the metal source, phosphorus source, carbonized resin powder and chopped carbon fiber is 50:7:100:1, and the weight ratio of the metal sources Fe2O3, Al2O3, Pb3O4, CaF2 and In2O3 is 1.75:1.5:1:0.5:0.25.
[0288] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.
[0289] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.
[0290] The carbon-carbon composite material prepared in this comparative example has the following characteristics:
[0291] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; non-carbon element nanoparticles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;
[0292] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.07 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.182:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.552:1;
[0293] (3) The main elements contained in the carbon-carbon composite material include: C content is 56 weight %; Fe content is 5.4 weight %; Al content is 4.3 weight %; P content is 2.2 weight %; Pb content is 3.0 weight %; Ca content is 1.0 weight %; In content is 0.8 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0294] Comparative Example 10
[0295] The method of Example 1 was followed, except that the gas flow rate was 10 mL / min.
[0296] The carbon-carbon composite material prepared in this comparative example has the following characteristics:
[0297] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by two layers of graphite sheets with a concentric circle structure, the thickness of the two layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the two layers of graphite sheets to the diameter of the single carbon fiber is 3:1; non-carbon element nanoparticles are attached to the surface of the single carbon fiber and each layer of graphite sheets; the diameter of the carbon-carbon composite material is 0.03mm, and the length is 3mm;
[0298] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.02 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value ratio of the peak intensity of the D peak to the G peak is 0.161:1, and the average value ratio of the peak intensity of the 2D peak to the G peak is 0.474:1;
[0299] (3) The main elements contained in the carbon-carbon composite material include: C content is 94 weight %; Fe content is 0.4 weight %; Al content is 0.1 weight %; P content is 0.1 weight %; Pb content is 0.05 weight %; Co content is 0.02 weight %; Ca content is 0.03 weight %; In content is 0.02 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.
[0300] Test Case
[0301] 1. The heat resistance of the materials prepared in the examples and comparative examples was tested according to the following method. The results are shown in Table 1.
[0302] Weigh about 3g of material in a high-temperature crucible and record the mass of the material as m1. (1) Heat treatment in a muffle furnace (air atmosphere, the same below), treatment temperature 500℃, keep warm for 2h, and cool naturally; (2) Treatment temperature 800℃, keep warm for 2h, cool naturally, take out, weigh and record the mass of the material as m2. Use the thermal weight loss rate (w, expressed as a percentage) of the material to indicate its heat resistance. The smaller the thermal weight loss rate, the better the heat resistance.
[0303] The thermal weight loss rate of the material is expressed by the following formula:
[0304]
[0305] 2. The sealing performance of the materials prepared in the examples and comparative examples was tested according to the following method. The results are shown in Table 1.
[0306] The material was pressed into a sample piece with a diameter of 25 mm and a thickness of 15 mm, and then finely processed and ground on each surface. Fig.10 On the device for testing sealing performance shown in FIG. 1 , the trimmed sample piece 7 is fixed between the first container 2 and the second container 3, and 2.0 MPa nitrogen is introduced from the gas inlet 6. The second container 3 is connected to one end of the pipe 5 with an inner diameter of 8 mm, and the other end of the pipe 5 is placed in the gas collection bottle 4 filled with pure water (the height difference Δh between the end of the pipe 5 and the liquid level of the gas collection bottle 4 is 20 mm). In this test, the leakage degree of the sample piece seal is analyzed by the number of bubbles in the gas collection bottle 4 per minute.
[0307] Table 1
[0308]
[0309] It can be seen from Table 1 that the material prepared by the technical solution of the present invention has a small thermal weight loss rate and good high temperature resistance; the number of bubbles collected per minute is small and the sealing performance is good.
[0310] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A carbon-carbon composite material with heat-resistant sealing performance, characterized in that: The carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, wherein non-carbon element nanoparticles are attached to the surfaces of the single carbon fiber and each layer of graphite sheets. The non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, optional Group IIA elements and optional indium.
2. The carbon-carbon composite material according to claim 1, characterized in that: The carbon-carbon composite material contains 50-90 wt % of carbon, 0.5-10 wt % of iron, 0.5-10 wt % of aluminum, 0.2-5 wt % of phosphorus, 0.2-5 wt % of lead, 0.2-5 wt % of cobalt, 0-1 wt % of Group IIA elements and 0-1 wt % of indium; Preferably, the carbon-carbon composite material contains 56-80 weight % of carbon, 5-8 weight % of iron, 4-8 weight % of aluminum, 1-3.5 weight % of phosphorus, 1-3.5 weight % of lead, 0.5-3.5 weight % of cobalt, 0.2-0.8 weight % of Group IIA elements and 0.2-0.8 weight % of indium.
3. The carbon-carbon composite material according to claim 1 or 2, characterized in that: The Group IIA element is selected from one or more of calcium, strontium and barium.
4. The carbon-carbon composite material according to any one of claims 1 to 3, characterized in that: The non-carbon element nanoparticles contain iron, aluminum, phosphorus, lead, cobalt, calcium and indium.
5. The carbon-carbon composite material according to any one of claims 1 to 4, characterized in that: The number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, more preferably 6-12 layers.
6. The carbon-carbon composite material according to any one of claims 1 to 5, characterized in that: The diameter of the single carbon fiber is 4-8 um, preferably 4.5-7.5 um; the length is 2-10 mm, preferably 3-9 mm.
7. The carbon-carbon composite material according to any one of claims 1 to 6, characterized in that: The thickness of the multilayer graphite sheet increases gradually from the inside to the outside; Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:
1.
8. The carbon-carbon composite material according to any one of claims 1 to 7, characterized in that: The carbon-carbon composite material is in a straight line and / or a curved shape; Preferably, at least part of the surface of the carbon-carbon composite material is in a bamboo-node shape and / or a convex shape; Preferably, the carbon-carbon composite material has a diameter of 0.05-1 mm, preferably 0.1-0.3 mm, and a length of 0.1-10 mm, preferably 1-5 mm.
9. The carbon-carbon composite material according to any one of claims 1 to 8, characterized in that: In the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1; Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak is 0.2-0.9:
1.
10. A method for preparing a carbon-carbon composite material with heat-resistant sealing performance, characterized in that: The method comprises: reacting chopped carbon fibers, a carbon source, a metal source and a phosphorus source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 20-1800 mL / min; The metal source contains an iron source, an aluminum source, a lead source, a cobalt source, an optional Group IIA element source and an optional indium source.
11. The method according to claim 10, characterized in that The weight ratio of the metal source, the phosphorus source, the carbon source and the chopped carbon fiber is 20-100:3-20:30-200:1, preferably 30-70:5-15:50-150:1; The weight ratio of the iron source, the aluminum source, the lead source, the cobalt source, the Group IIA element source and the indium source is 0.8-4:1-4:0.3-1.5:1:0-1:0-0.
5.
12. The method according to claim 10 or 11, characterized in that: The Group IIA element source is selected from one or more of a calcium source, a strontium source and a barium source.
13. The method according to any one of claims 10 to 12, characterized in that: The metal source contains an iron source, an aluminum source, a lead source, a cobalt source, a calcium source and an indium source; Preferably, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4; Preferably, the aluminum source is selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4; Preferably, the lead source is selected from one or more of PbO, Pb3O4, PbO2 and Pb2O3; Preferably, the cobalt source is selected from one or more of CoO, Co(OH)2, CoCl2 and CoSO4; Preferably, the calcium source is selected from one or more of CaCl2, CaO, Ca(OH)2 and CaF2; Preferably, the indium source is selected from one or more of In2O3, In(OH)3 and InCl3.
14. The method according to any one of claims 10 to 13, characterized in that: The phosphorus source is selected from one or more of FePO4, AlPO4, Al(PO3)3 and Ca3(PO4)2.
15. The method according to any one of claims 10 to 14, characterized in that: The carbon source is carbonized resin and / or graphite; Preferably, the graphite is amorphous graphite.
16. The method according to any one of claims 10 to 15, characterized in that: The reaction temperature is 1500-3000°C; the reaction time is 12-720 hours, preferably 24-120 hours; Preferably, the volume flow rate of the inert atmosphere is 50-500 mL / min, preferably 100-300 mL / min.
17. The method according to any one of claims 10 to 16, characterized in that: The length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95% by weight.
18. A carbon-carbon composite material with heat-resistant sealing properties prepared by the method according to any one of claims 10 to 17.
19. Use of the carbon-carbon composite material with heat-resistant sealing performance as claimed in any one of claims 1 to 9 or the carbon-carbon composite material with heat-resistant sealing performance as claimed in claim 18 as a heat-resistant sealing material.
Citation Information
Patent Citations
Carbon-carbon composite material as well as preparation process and application thereof
CN111807853A
Manufacturing process of carbon-carbon composite material
CN112125690A
Preparation method of flexible carbon-carbon composite material
CN112679950A
Thin-wall high-strength carbon-carbon composite material pipeline and preparation method thereof
CN113175565A
Internal antioxidant carbon-carbon composite material
CN113636855A